Public Sector Innovation in Smart Village Development for the Cikupa Village Community, Cikupa Sub-District in Tangerang District - Muhamad Rafli Kurniawan; Udin Syamsudin; Thita Moralitha Mazya (Peneliti.net, 2023)
This study aims to determine how public sector innovation in Cikupa Village and how the Sustainability of Smart Village Development for the Cikupa Village Community in Cikupa Subdistrict in Tangerang Regency in the Future. The object of this research is data on Smart Village Development Public Sector Innovation in Cikupa Village Community, Cikupa Subdistrict, Tangerang Regency. This research uses a qualitative approach research paradigm with descriptive research type. The nature of the research used in this research is descriptive qualitative research. The research type uses descriptive research patterns. The research data sources are divided into 2, namely primary data sources and secondary data sources. The data collection stage in this study consists of observation, interviews and documentation. Qualitative data analysis techniques, namely, data collection, data reduction, data presentation and drawing conclusions. The results showed that of the five dimensions, it can be concluded that the public sector innovation in developing a smart village for the Cikupa Village community in Tangerang Regency is in accordance with the five dimensions of innovation proposed by Everett M. Rogers, namely relative advantages, compatibility, trialability, observability. However, the complexity dimension is still considered insufficient and the sustainability of Smart Village in Cikupa Village, Tangerang Regency, is illustrated by the long-term planning of the village apparatus and the development of the Simpel Desa application, which continues to be improved and upgraded.